Interferon Response to Mitogens and Viral Antigens in Elderly and Young Adult Subjects - Rytel, M. W.; Larratt, K. S.; Tuner, P. A.; Kalbfleisch, J. H. (The Journal of infectious diseases, 1986)
Herpes zoster, a disease thought to be due to reactivation of varicella-zoster virus (VZV), is more common in elderly individuals than in the rest of the population. Hope-Simpson reported the disease to be relatively uncommon until the age of 50 years, after which there is a steep rise in incidence rates. Mechanisms responsible for this disease are not known. Because humoral immunity to VZV is not diminished in elderly individuals, recent studies have focused on cell-mediated immunity. Results of these studies were variable. gamma -Interferon (IFN- gamma ) is a lymphokine thought to be of importance in immunoregulation and resistance to viral infections.